2020
DOI: 10.1111/sms.13845
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness, physical activity, sedentary behavior, and circulating white blood cells in US youth

Abstract: The white blood cell (WBC) count indicates the number of white blood cells (ie, neutrophils, lymphocytes, monocytes, basophils, and eosinophils) in a sample of blood. High or extremely low total WBC counts in circulation at resting conditions could be related to the presence of illness. White blood cells are made in the bone marrow and protect the body against infection and aid in the immune response. 1 Importantly, the WBC count is considered a clinical marker that reflects inflammatory processes related to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
0
11
1
Order By: Relevance
“…For this reason, these findings could be relevant since increased BMI in childhood and adolescence might be linked to faster ageing and could have a harmful impact on future health later in life [ 29 ]. Conversely, another study using the present sample showed an inverse relationship between WBC count, cardiorespiratory fitness and habitual physical activity levels [ 10 ]. People who were physically active or had high aerobic fitness potentially participated in activities that benefited their muscular fitness levels [ 30 ], which could explain (at least partially) our results.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…For this reason, these findings could be relevant since increased BMI in childhood and adolescence might be linked to faster ageing and could have a harmful impact on future health later in life [ 29 ]. Conversely, another study using the present sample showed an inverse relationship between WBC count, cardiorespiratory fitness and habitual physical activity levels [ 10 ]. People who were physically active or had high aerobic fitness potentially participated in activities that benefited their muscular fitness levels [ 30 ], which could explain (at least partially) our results.…”
Section: Discussioncontrasting
confidence: 61%
“…According to the relationship between the immune system and muscular fitness, a recent systematic review and meta-analysis performed by Tuttle et al [ 7 ] indicated that higher systemic inflammation is linked to lower muscle strength and muscle mass in humans. Conversely, only a few studies [ 8 , 9 , 10 ] have examined the relationships between WBC counts and cardiorespiratory fitness, physical activity and sedentary behavior among children and adolescents. Nevertheless, the role of muscular fitness (as a protecting factor for an optimal immune system) and WBC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…We observed an inverse association between leisure-time physical activity level and WBC count. Large observational studies consistently reported that individuals performing more frequent or more intense physical activity, regardless of leisure-time or total physical activity, had a lower WBC count (17,20,22,23,28,30,31). A higher objectively measured moderate-to-vigorous physical activity level was associated with a lower WBC count in the US adult population, healthy US male population, and US youth population in previous NHANES studies (17,20,30).…”
Section: Discussionmentioning
confidence: 80%
“…Leisure time physical activity is any physical activity outside of work and may include both intensive and non-intensive activities. Previous reports have observed an association between physical activity level and speci c peripheral immune cell populations in various populations (17)(18)(19)(20). Of total physical activity, higher levels of moderate-to-vigorous physical activity, measured objectively, was associated with a lower WBC count (20).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation